P229 IMPROVED CLINICAL–INSTRUMENTAL OUTCOMES IN PATIENTS WITH CHRONIC DILATED HYPERTENSIVE / ISCHEMIC HEART DISEASE, UNDERGOING CCM, CARRIER OF CRTD WITH PERSISTENT SEVERE LEFT VENTRICULAR DYSFUNCTION. (18th May 2022) - Incampo, G; De Luca, V; Rizzo, D; Bux, F; Moramarco, M; Valecce, R; Robles, G; Pirozzi, M; Candida, T; Marino, F; Campagna, M; Fiorentino, A; et al.
Abstract: A 62–year–old man repeatedly subjected to PTCA + stent with severe left ventricular dysfunction and estimated FE 15%. After some hospitalizations for heart failure in 2015 he underwent an AICD implant Biventricular. Followed up in our clinics dedicated to heart failure, the patient did not present the characters of the CRT responder presenting a constant high end–systolic volume (224 ml) and none FE improvement of 15%. There was also an asthenia and tendency to inactivity and elevated NT Pro BNP levels despite optimal medical therapy even with entresto 24/26 mg x 2 / day. It has been decided to submit the patient enrolled in the cardiac transplant and / or VAD implantation lists to an implantation procedure of CCM system (cardiac contractility modulation). After two active fixation placement leads on the interventricular septum and connection to the CCM system housed in the subcutaneous pocket right contralateral to the biventricular AICD, the patient was monitored. We have noticed since the first days conditions of hemodynamic stability. Scheduled CCM therapy delivery for 10 hours a day. Following subsequently in the follow up at 3 – 6 – 12 – 18 months the patient showed an improvement of minneshota quality of life questionnaire in heart failure: MLWHFQ (44 at baseline, 17 at two months, 15 to six months, 10 to 12 months and 3 to 18 months), an increase in FE from 15 to 23 up to 26%, a reduction of the NTPROBNP from 13444 to 1178 then climbed back to 5549 and 3712 at 18 months for atrial fibrillation, without any requires re–hospitalization, an increased physical activity of the patient detected by the sensors of the two devices